Investigating the Relationship between Organizational Citizenship Behavior, Organizational Support, and Organizational Culture with Employee Job satisfaction (Case Study: Personnel of Foundation of Martyrs and Veterans Affairs in Fars Province) - Roudbar, Raziyeh Kazemi; Fazlollahi, Seifollah; Moghadam, Ali Akbar Khoshgoftar (International Journal of Psychosocial Rehabilitation, 2020)
Employee job satisfaction is one of the most important variables in the field of organizational behavior and it is not possible to achieve organizational goals without it. The purpose of this study was to investigate the relationship between the pattern of organizational citizenship behavior, organizational support and organizational culture on the personnel’s job satisfaction of Foundation of Martyrs and Veterans Affairs in Fars Province. This was a descriptive-survey research method and statistical population was consisted of all personnel for Foundation of Martyrs and Veterans Affairs in Fars Province (466 people). The sample size was estimated 210 using Cochran’s formula. Data collection tool included the Podsakoff Citizenship Behavior Questionnaire, Eisenberger Organizational Support Questionnaire, Robbins Organizational Culture Questionnaire, and Smith et al. Job Satisfaction Questionnaire. Data analysis was performed using 21-SPSS and Amos software. The results showed that organizational culture, organizational support and organizational citizenship behavior had a positive and significant effect on personnel’s job satisfaction of Foundation of Martyrs and Veterans Affairs in Fars Province. Also, the structural equation model showed that the variable of organizational support with direct effect (0.628) explained the highest value of job satisfaction variance.